KONTEK DAN REFERENSI WACANA IKLAN AJINOMOTO VERSI BAHASA JEPANG - Wibisono, Lutfhi Kastantyo; Ratna, Maharani; Trahutami, Sriwahyu (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
This research is dealing about discourse context and reference. This researchdescribe the discourse context and reference in Advertisement. From context weknow about setting, participant, norms, genre, key, message, ends, and instrument.for analysis of reference of this advertisement was found that personal pronoun 1is (watashi) 4, (anata) 5, (atashi) 1, (ore) 2, (kimi) 1, (kare) 1, and for thepersonal pronoun 3 found (watashitachi) just 1. Next for demonstrative pronounanalysis, found first, (are) 1, (sore) 2, (kore) 3, (sonna) 2, (konna) 2, (soko) 1,(kono) 1, koitsu (2). In the analysis of this advertising is not found comparativepronouns in advertisement.